Pemanfaatan Tumbuhan Obat Masyarakat Marind yang Bermukim di Taman Nasional Wasur, Merauke - Dwi Haryanto; Rosye H.R. Tanjung; Konstantina M.B. Kameubun (Jurnal Biologi Papua, 2009)
Study on the used of medicinal plants by Marind people who lived at Wasur National Park, Merauke was conducted by using descriptive methods which include observation, interview, documentation, literature review techniques, as well as  emic and ethic approaches. During the study there were 46 species which belong to 26 families plants found as medicinal plants used by Marind people to cure about 30 diseases. Among 46 species, there were 7 potential medicinal plant species which known  and used by most Marind people. The seven potential medicinal plant species were Ipomoea triloba L., Bauhinia sp., Pittosporum sp., Kingiodendron platycarpum Bent., Sophora tool mentosa L.Cyrtandra sp., dan Tinopspora disstiflora L. Part of plant used vary from leaf, root, bark, fruit and other part of plant. Compare to other part of plant, leaf was the most common used as traditional medicinal plant. Key words:   traditional medicinal plant, Marind people, Wasur National Park